From My Home to Our Home, Towards the Contemporary Collaborative Events - Bakalchev, V., Tasic, S., Hadzi Pulja, M., Bakalchev, M (My University, 2018)
Hospitality, donation, and sharing are the essence of many residential cultures. Hospitality to another, sharing one’s home, one’s meal, one’s words, one’s beliefs, and participating in collective events are a part of the various housing practices that are a basis of our communities. Can we recognize these traditional models in modern society? Can this aspect of housing and community be productive, or even be a model for our housing practice today? We live in a contradictory world that is at the same time subjectively centered and homogenized and whose consequences are fragmented communities and spaces. However, we could still find authentic traces of our common living. This paper will introduce different experiences from the joint events in the cities and villages of the Republic of Macedonia and will link them to the specific places and spaces they shape and from which they evolve. They arise from traditional events, but they are all transformed into contemporary situations: St. Ilija Day (Ilinden) and construction of a church in the village of Govrlevo, a garden in the village of Velmei, and bonfire gatherings before Christmas in the settlements in Skopje. They will show us: how a long-term reconstruction / renovation of the church of St. Ilija,inspired and stirred the interest to be together on the Day of St. Ilija and the various events organized by the inhabitants of the almost abandoned village of Govrlevo; how building a private garden in the village of Velmej can be the physical framework for various collective events of the inhabitants of the village; how the traditional gathering and collective bonfires before Christmas in the neighborhoods of Skopje, encourage a new inclusive practice and identity of the people which hail from the fragmented old neighborhood. All these practices are contemporary phenomena and they continue from traditional models, but are reproduced and sometimes opposed by the official views of the authorities, and they are the living events of today's people. In a way they represent the traditional values, but also the contemporary opportunities for unity.
Keywords: traditional patterns, collaborative events, places, urban fragment